Neoplastic potential of odontogenic cysts - Zama Moosvi; S Amsavardani Tayaar; G S Kumar (Wolters Kluwer Medknow Publications, 2011)
Odontogenic cysts and tumors are distinct entities and quite a common occurrence in the jaw bones. The lining of odontogenic cysts shows a potential for neoplastic transformation to non odontogenic malignancies like squamous cell carcinoma and mucoepidermoid carcinoma, and odontogenic tumors like ameloblastoma and adenoamatoid odontogenic tumor (AOT). AOT is a benign, epithelial odontogenic tumor, common site being the anterior maxilla. Its origin from a dentigerous cyst and in the mandible is rare. A case of an AOT arising from a dentigerous cyst associated with an impacted permanent mandibular left lateral incisor is reported.